2011
DOI: 10.14710/jitaa.36.3.152-158
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Reproductive Traits in Bali Cattle Maintained on Range Under Artificially and Naturally Bred

Abstract: The aim of this study was to evaluate genetic analysis including heritability and further phenotypic and genetic trends of reproductive traits in Bali cattle. Reproductive traits studied were age at first calving (AFC), calving interval (CI) and pregnancy rate (PR). Data of reproductive traits were collected from Breeding Centre of Bali Cattle, Denpasar-Bali at the year period of 2000-2007. To evaluate the genetic analysis, heritability were estimated using the Mixed Model Least Squares and Maximum Likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Gunawan et al (2011b) considered that this might be partly a correlated response to selection for increased daily gain. A possible cause of the undesirable trend in gestation length and of the marked fluctuation of values observed for AFC, CI, and DO could be the intense selection to increase productive traits (Lopes et al, 2011;Santos et al, 2012;Lopes et al, 2013), without giving attention to reproductive traits.…”
Section: Discussionmentioning
confidence: 99%
“…Gunawan et al (2011b) considered that this might be partly a correlated response to selection for increased daily gain. A possible cause of the undesirable trend in gestation length and of the marked fluctuation of values observed for AFC, CI, and DO could be the intense selection to increase productive traits (Lopes et al, 2011;Santos et al, 2012;Lopes et al, 2013), without giving attention to reproductive traits.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight showed no definite trend that indicated low degree of R 2 except 18WM for genetic and phenotypic trend. The low degree of genetic progress for body weight can be explained mainly by selection program and this may slow down genetic progress (Gunawan et al, 2011).…”
Section: Genetic and Phenotypic Trendsmentioning
confidence: 99%
“…Furthermore, Jarkovska et al (2011) reported that in women with severe ovarian hyper stimulation syndrome, complement C3 was expressed differentially. In our study, the detection of complement C3 in BcFF whether related to the reproductive nature of Bali cattle (Gunawan et al, 2011), challenge the researchers to elucidate what the role of BcFF complement C3 is on the Bali cattle reproductive system. In addition to complement C3, in this study, antitestosterone antibody was also identified in the BcFF.…”
Section: Resultsmentioning
confidence: 87%
“…Bali cattle are Indonesian native cattle, which has been developed from domesticated banteng, Bos javanicus, Bos banteng (Nijman et al, 2003;Mohamad et al, 2009). Bali cattle are also considered to have moderate to high (0.21-0.41) reproductive heritability, which means that Bali cattle have the potential to be genetically improved through selection programs, with good reproductive management practices (Gunawan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%